PEMANFAATAN BUAH MANGROVE UNTUK PENINGKATAN PEREKONOMIAN MASYARAKAT DI DESA DUNU KABUPATEN GORONTALO UTARA - Darmawan, M; Handayani Arifin, Tuti; Megasari, Ria; Suleyman; Rasyid, Magfirah (Education and Talent Development Center of Indonesia, 2025)
This community service activity focuses on developing mangrove-based coffee products as part of an effort to innovate the processing of non-timber forest products with high potential in the coastal areas of North Gorontalo. This activity was carried out in response to the high potential of mangrove ecosystems that have not been optimally utilized by coastal communities, particularly in the context of downstreaming products based on the creative economy. The community service was carried out through a series of stages, starting from identifying safe and edible mangrove species, training local community groups, developing mangrove coffee product formulations, and providing marketing assistance. The methods used in this program included counseling, technical production training, branding and marketing workshops, and business sustainability evaluations. Through a participatory approach, coastal communities, particularly women and youth groups, were actively involved in the entire process, facilitating knowledge and technology transfer while empowering the economy. The results showed improved skills in producing mangrove coffee, the establishment of local marketing networks, and the emergence of new entrepreneurial spirit among beneficiaries. Mangrove coffee products have also received positive feedback from both local consumers and tourists due to their uniqueness and added value. This initiative is expected to encourage the diversification of coastal flagship products, increase community income, and promote synergy in the conservation of mangrove ecosystems in North Gorontalo. The active participation of local government stakeholders and related institutions is also key to the sustainability of the program for the development of the coastal region's creative economy.